Diagnostic utility of CT in differentiating between ruptured ovarian corpus luteal cyst and ruptured ectopic pregnancy with hemorrhage - Xiaohong Liu; Litao Song; Jian Wang; Qin Liu; Yingna Liu; Xin Zhang (Journal of Ovarian Research, 2018)
Abstract Background To evaluate the performance of computed tomography (CT) as a diagnostic aid to differentiate between ruptured ovarian corpus luteal cyst (ROCLC) and ruptured ectopic pregnancy with hemorrhage (REPWH). Methods A total of 36 patients treated at our hospitals for ROCLC and REPWH from June 2014 to August 2017 were included in this study. Based on the diagnosis, the study population was divided into ROCLC group (n = 21) and REPWH group (n = 15). CT scans were performed for all patients prior to treatment. The size of the cystic shadows and the depth of the pelvic effusion were analyzed and compared with independent sample Student’s t test and Fisher’s exact test. Results Cystic shadows with maximum diameters ≥3.0 cm presented in 16 patients with ROCLC and 1 patient with REPWH, while 4 patients with ROCLC and 9 patients with REPWH exhibited cystic shadows with maximum diameters <3.0 cm. The mean diameters along the major and minor axes in the two groups were 3.76 ± 1.11 cm and 2.93 ± 0.98 cm, 1.96 ± 0.65 cm and 1.60 ± 0.55 cm, respectively (p < 0.001). The mean depth of the pelvic effusion in patients with ROCLC and REPWH were 5.20 ± 2.47 cm and 6.96 ± 2.07 cm, respectively (p = 0.038). Conclusion The cystic shadow of ROCLC is larger than that of the REPWH. The depth of the pelvic effusion of REPWH is deeper than that of the ROCLC. CT can help differentiate between ROCLC and REPWH based on the size of the cystic shadow and the depth of pelvic effusion in the adnexal area.